Development of Streambed Potholes and the Role of Grinding Stones - Das, Balai Chandra (Journal of Environmental Geography, 2018)
The largest grinding stone episodically stored in pothole is not only responsible for growth of pothole size but also determines its shape. This paper examines the largest grinding stone found in cylindrical potholes and their role in pothole growth using empirical analysis. The largest grinding stone from 34 randomly selected potholes, developed on the riverbed of Subarnarekha River at Ghatshila, Jharkhand, India, were analyzed to have an insight into 1) their sizes and shapes; 2) controls on grinding stone shape; and 3) roles of largest grinding stone on streambed pothole growth. Strong correlation coefficient between the size and weight of grinding stones reveals their similar specific gravity. The pothole depth was proportional to the diameter of the largest grinding stone in it. Concave pothole-floors developed because of abrasion by grinding stones atop floor. A force applied on largest grinding stone depends upon not only eddy velocity within pothole but also on shape of the stone.